Techno-economic evaluation of third-generation bioethanol production utilizing the macroalgae waste: A case study in Malaysia - Chong, T.Y. (Elsevier Ltd, 2020)
Production of third-generation bioethanol from macroalgae cellulosic residue (MCR) has received increasing interest from researchers to utilize waste for valuable product creation effectively. In this study, a techno-economic assessment to produce anhydrous bioethanol from MCR in Malaysia had been conducted by using Aspen Plus V10 and other computer-aided softwares. Kota Kinabalu Industrial Park at Sabah was identified and selected as a proper location to produce the anhydrous bioethanol based on a framework structured by the Triple Bottom Line. The overall results from the present study showed that 15833.3 kg/h of MCR was required to produce 7626 kg/h of anhydrous bioethanol. It was also found that the energy utilization could be reduced up to 32 with net energy ratio of 0.53 after implementing the Heat Exchanges Networks Synthesis and a series of process optimization. In 20 years of plant life, the pay-back period was 8 years with an internal rate of return of 23.17. The minimum selling price of anhydrous bioethanol was estimated to be 0.54/kg and able to compete with the market prices of bioethanol derived from other feedstocks. Â© 2020 Elsevier Ltd